Challenges and opportunities for a successful mining industry in the future - A., Mateus (2019)
Modern models of sustainable economic growth are metal-intensive and will not be successful in the future unless a continuous supply of mineral-derived products is ensured. Despite this being logical, there is still a significant reluctance regarding mineral exploration and mining activities, often reflected in: (i) unfavourable public opinions; and (ii) absence of political measures or continuity of agendas that actually appreciate the way minerals are produced and the players directly or indirectly involved in this production. To succeed, the mining industry will have to (re)define its strategy and find innovative approaches to old problems and clearly demonstrate that mineral products can be efficiently delivered to support global development and assist suitable paths to welfare and quality of life, thus also providing real value to all concerned. In this study we give a concise review of the main challenges posed to the mining industry, and also indicate the most relevant opportunities and advance some proposals to constructively face the identified weaknesses and threats. The fundamental outcome is that the long-term balance between supply and demand of mineral products requires concerted actions on different fronts aiming: (i) the safeguarding of known resources; (ii) high-quality (scientifically and technologically driven) exploration surveys; (iii) improvements in mining and mineral transformation/ beneficiation; (iv) advances in consistent combinations of primary and secondary sources of raw materials, along with higher concerns on their judicious use; (v) effective and stable mining policies; and (vi) new insights on the role played by the mining industry through fruitful dialogues with society in general.